PENGGUNAAN E-MAIL PRIBADI DALAM MENUNJANG PRODUKTIVITAS KERJA PEGAWAI REKTORAT UNIVERSITAS HALU OLEO - samin samin (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2016)
Abstract Samin (C1D1 12 245) E-Mail Use of Personal In Supporting Work Productivity Employees Under haluoleo university, guidance by Sutiyana Fachruddin, S. Sos., M.Ikom as mentors I, and Saidin, S.Ip., M.Sc. as mentors II. The problems discussed in this study is how to Use Personal E-Mail In Supporting Work Productivity Employees haluoleo university , The purpose of this study is to investigate the use of Personal E-Mail to support the Employee Work Productivity Rektorat halu oleo university with a focus on how to use E-Mail to support the ongoing activities of the tasks that are urgent, such as data nominative lecturers, the data PUPNS, DUK, as well as civil servants regist Card. The study analysis using Domain analysis consisting of analysis, the data prior to the field, the data analysis, for in the field, and analysis final data field. Methodology This study was conducted in a way, literature study, field research, in-depth interviews, observation, and documentation. These results indicate that the use of E-Mail is very important in supporting tasks that are urgent. resulting in the effectiveness and efficiency of work. Use of E-Mail Personal Effectiveness And Efficiency Work Against Employees